2021
DOI: 10.1038/s41598-021-84656-1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of myotonometry for assessing muscle viscoelastic properties in patients with stroke: a systematic review and meta-analysis

Abstract: There is a lack of consensus about the measurement of the muscle viscoelastic features in stroke patients. Additionally, the psychometric properties of the most-commonly used clinical tools remain controversial. Our objective is to investigate the validity and reliability of myotonometry to assess viscoelastic muscle features in stroke survivors. Pubmed, PEDro, Scopus and Cinahl were systematically searched to include studies reporting the psychometric properties of myotonometric devices used in people after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
(140 reference statements)
0
34
0
Order By: Relevance
“…This myotonometer assesses the muscle's tone, biomechanical and viscoelastic properties using five parameters by means of dynamic oscillation mechanosignals [81,111] (Table 3). The MyotonPRO is a valid and reliable measurement tool for healthy and diseased participants [112,113] (Box 4) that has been applied to evaluate muscle tone, muscle stiffness, and HRMT in multiple studies investigating various structures and conditions [71,81,93,[114][115][116]. The myotonometer measurements were carried out at all three sessions (t1-t3) before and after the treatment intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This myotonometer assesses the muscle's tone, biomechanical and viscoelastic properties using five parameters by means of dynamic oscillation mechanosignals [81,111] (Table 3). The MyotonPRO is a valid and reliable measurement tool for healthy and diseased participants [112,113] (Box 4) that has been applied to evaluate muscle tone, muscle stiffness, and HRMT in multiple studies investigating various structures and conditions [71,81,93,[114][115][116]. The myotonometer measurements were carried out at all three sessions (t1-t3) before and after the treatment intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Myotonometry is a valid and easy-to-use approach to objectively quantify muscle mechanical properties in people after stroke. 4,6 However, its high environmental sensitivity 4 and the large withinand between-participants variability 19 together with assessmentrelated aspects, such as muscle position and operator's experience, 4,20 stress the importance of agreeing on a standardized evaluation protocol.…”
Section: Comparison Between Measurement Protocolsmentioning
confidence: 99%
“…The peripheral contribution to poststroke spasticity (PSS) can be quantified for clinical and research purposes using objective, noninvasive methods, for example, shear-wave elastography and myotonometry. 4,5 Myotonometry represents a valid, reliable, and convenient tool 4,6 that has proven to be useful to monitor PSS after conservative or invasive treatments. 7 However, current evidence on the ability of myotonometry to discriminate between spastic and nonspastic muscles after stroke is scarce and conflicting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, their high cost makes them inaccessible to a clinical setting, challenging the determination of the MMPs. Since a decade ago, the device MyotonPRO© emerged as a non-invasive and reliable alternative to assess and monitor MMPs with clinical applications Several studies have shown sufficient accuracy and precision to determine MMPs in spinal muscles [ 23 , 24 , 25 , 26 ] and other tissues and regions [ 23 , 27 , 28 , 29 ], although efforts to better determine the concurrent validity need further research [ 30 ]. Previous research has associated MMPs alterations, specifically an increase in stiffness and tone or a decrease in elasticity, and axial spondyloarthritis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%